Field and temperature dependence of the photocurrent in polymer/fullerene bulk heterojunction solar cells - Gommans, Hendrikus Hubertus Petrus; Kemerink, Martijn; Kramer, J. M.; Janssen, René A. J. (Applied physics letters, 2005)
The photocurrent in polymer/fullerene blends is characterized as a function of bias at temperatures ranging from 125to300K125to300K125<mspace width="0.3em"></mspace><mtext>to</mtext><mspace width="0.3em"></mspace>300<mspace width="0.3em"></mspace>K. Assuming a constant generation rate and bimolecular recombination, the results are numerically modeled within the drift-diffusion approximation. Bimolecular recombination is found to be a dominant factor in the field dependence of the photocurrent in the entire measured voltage range. Inclusion of field dependent geminate pair dissociation and recombination via the Onsager expressions gives a much stronger field dependence than experimentally observed. From the temperature dependence of the extracted mobilities, we can simultaneously estimate the broadening of the transporting highest occupied and lowest unoccupied molecular orbital levels.
Gesehen am 11.12.2019